The Role of Keratin17 in Human Tumours - Zhang, Hanqun; Zhang, Yun; Xia, Tingting; Lu, Liang; Luo, Min; Chen, Yanping; Liu, Yuncong; Li, Yong (Frontiers in Cell and Developmental Biology, 2022)
Keratins are a group of proteins that can constitute intermediate fibers. It is a component of the cytoskeleton and plays an important role in cell protection and structural support. Keratin 17, a Type I keratin, is a multifunctional protein that regulates a variety of biological processes, including cell growth, proliferation, migration, apoptosis and signal transduction. Abnormal expression of KRT17 is associated with a variety of diseases, such as skin diseases. In recent years, studies have shown that KRT17 is abnormally expressed in a variety of malignant tumours, such as lung cancer, cervical cancer, oral squamous cell carcinoma and sarcoma. These abnormal expressions are related to the occurrence, development and prognosis of malignant tumors. In this review, we summarized the expression patterns of KRT17 in a variety of malignant tumours, the role of KRT17 in the development and prognosis of different malignant tumors and its molecular mechanisms. We also discuss the potential clinical application of KRT17 as a valuable therapeutic target.